Description of three new species of Labena Cresson from Mexico (Hymenoptera, Ichneumonidae, Labeninae), with notes on tropical species richness - González-Moreno, Alejandra; Bordera, Santiago; Sääksjärvi, Ilari Eerikki (Zootaxa, 2015)
Three new species of Labena Cresson (Ichneumonidae, Labeninae); L. littoralis sp. nov., L. tekalina sp. nov. and L. madoricola sp. nov. are described and illustrated. Material was collected with Malaise traps in 2008 and 2009 in the Biosphere Reserve Ria Lagartos (Mexico). Diagnostic characters to distinguish them from all other New World species of the genus are provided. In addition, the tropical species richness of the genus is shortly discussed.